2019
DOI: 10.3390/nu11122951
|View full text |Cite
|
Sign up to set email alerts
|

Organic Consumer Choices for Nutrient Labels on Dried Strawberries among Different Health Attitude Segments in Norway, Romania, and Turkey

Abstract: Consumer interest towards healthy food is driving the growth of the organic food market because consumers perceive organic food products to improve their personal health. Berries have well-known health benefits and show increasing market shares in European markets. This manuscript investigates for the first time how health attitudes relate to organic consumers’ choices for nutrient labels of organic dried strawberry products. We conducted an online survey with 614 consumers from Norway, Romania, and Turkey. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 84 publications
(111 reference statements)
1
10
0
Order By: Relevance
“…Consumer interest in healthy food contributes to the development of the organic food market as the customers believe that organic food improves their health [69,70]. Various studies have shown that health-conscious people are more likely to buy organic food.…”
Section: Discussionmentioning
confidence: 99%
“…Consumer interest in healthy food contributes to the development of the organic food market as the customers believe that organic food improves their health [69,70]. Various studies have shown that health-conscious people are more likely to buy organic food.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ballco and De Magistris [66] identified three consumer segments: "health-claims oriented", "nutritional-and health-claim oriented", and "indifferent". There is a complexity of targeting nutrition labels because a nonlinear effect of health attitude on the selection of products with increased nutrients content was revealed in previous research [67].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies (for instance, Aguirre & Tumlty, 2001;Almli et al, 2019;Hempel & Hamm, 2016;The Packer, 2001;Wolf, 2002;Yue & Tong, 2009) have investigated the effect of organic quality attributes and other characteristics on consumer preferences. However, empirical evidence supports a hypothesis that product quality characteristics affect consumers' preferences for organic food, with the most important being: nutritive value; economic value; freshness; flavour/taste; ripeness; and general appearance "especially of fruits and vegetables."…”
Section: Consumer Preference On Organic Food Consumptionmentioning
confidence: 99%